Primary health care as a tool to promote equity and sustainability; a review of Latin American and Caribbean literature - Maceira, Daniel Alejandro (2024)
AbstractPrimary health care (PHC) has increased in global relevance as it has been demonstrated to be a useful strategy to promote community access to health services. Multilateral organizations and national governments have reached a consensus regarding the basic principles of PHC, but the application of these varies from country to country due to the particularities of local health systems.This article aims to review and summarize PHC strategies and the configuration of health networks in Latin American and Caribbean countries.The review was carried out using keywords in at least 9 databases. Papers in languages other than English, Portuguese, and Spanish were excluded, while non-refereed articles and regional gray literature were incorporated. As a result, 1,146 papers were identified. After three instances of analysis, 142 articles were selected for this investigation. Data were analyzed according to an analysis by theme.The evidence collected on health reforms in the region reflects the need to intensify care strategies supported by PHC and care networks. These must be resilient to changes in the population’s needs and must be able to adapt to contexts of epidemiological accumulation.